Willingness to participate in cardiac telerehabilitation: results from semi-structured interviews. Issue 1 (22nd October 2021) - Falter, Maarten; Scherrenberg, Martijn; Kindermans, Hanne; Kizilkilic, Sevda; Kaihara, Toshiki; Dendale, Paul
Abstract: Aims: Cardiac rehabilitation (CR) is indicated in patients with cardiovascular disease but participation rates remain low. Telerehabilitation (TR) is often proposed as a solution. While many trials have investigated TR, few have studied participation rates in conventional CR non-participants. The aim of this study was to identify the percentage of patients that would be willing to participate in a TR programme to identify the main perceived barriers and facilitators for participating in TR. Methods and results: Two groups of patients were recruited: CR non-participants and CR participants. Semi-structured interviews were conducted. Thirty non-participants and 30 participants were interviewed. Of CR non-participants, 33% would participate in TR and 10% would participate in a blended CR programme (combination of centre-based CR and TR). Of CR participants, 60% would participate in TR and 70% would be interested in a blended CR programme. Of those that would participate in TR, 44% would prefer centre-based CR, 33% would prefer a blended CR programme, and 11% would prefer a full TR programme. In both groups, the main facilitating aspect about TR was not needing transport and the main barrier was digital literacy. Conclusion: For CR non-participants, TR will only partly solve the problem of low participation rates and blended programmes might not offer a solution. Cardiac rehabilitation participants are more prepared to participate in TR and blended CR. Digital literacy was in both groups mentioned as an important barrier, emphasizing the challenges for healthcare and local governments to keep educating all types of patients in digital literacy. Graphical abstract: